The risk of helminth infections at Endangered Primate Rescue Center, Cuc Phuong National Park Vietnam. Issue 1 (June 2021) - Vu, Hoai-Nam; Cong, Ha-My; Tran, Nam-Trieu; Vo, Duy-Thanh; Rowley, C; Anh Le, T L; Nguyen, Thi-Nhien; Bui, Khanh-Linh
Abstract: To clarify the transmission route of parasitic infections in primates at Endangered Primate Rescue Center, Cuc Phuong National Park, we investigated the prevalence of intestinal helminths in leaf and dog fecal samples collected in the surrounding areas of the center. By morphological analysis, only Ancylostoma spp. and Isospora spp. were detected in leaf samples, with the infection rate of 7.07% and 1.01% respectively. In addition, survey on 156 dog feces samples showed that the overall prevalence of gastrointestinal parasites was quite high (73.55%). Ancylostoma spp has the highest prevalence (68.39%), followed by Toxocara spp. (25.81%), Trichuris spp. (10.97%), Isospora spp. (7.1%) and Taenia spp (3.87%).